Dynamic improvement of fatigue strength via local phase transformation in a circumferentially-notched austenitic stainless steel under fully-reversed loading condition. (February 2020) - Nagaishi, Naoaki; Okazaki, Saburo; Ogawa, Yuhei; Matsunaga, Hisao
Abstract: The fatigue limit of a circumferentially-notched austenitic stainless steel exhibited peculiar improvement under fully-reversed loading ( R =−1), as compared with that under tension-tension loading ( R  = 0.1), behavior considered to be unconventional in smooth specimens of similar materials. This was attributed to the different cyclic stress-strain responses at the notch-root, where it was almost elastic at R  = 0.1, whereas an elasto-plastic response continued up to later stage of the fatigue process at R =−1. Such cyclic plasticity enhanced martensitic transformation locally and resulted in hardening, thereby restricting fatigue crack initiation from the notch-root. Graphical abstract: Image, graphical abstract